New insight into the causal linkage between economic expansion, FDI, coal consumption, pollutant emissions and urbanization in South Africa - Udi Joshua; Festus Victor Bekun; Samuel A. Sarkodie (African Governance and Development Institute (AGDI), 2020)
This study examines the relationship between foreign direct investment inflows and economic growth by incorporating the role of urbanization, coal consumption and CO2 emissions as additional variables to avoid omitted variable bias. The different order of integration from the unit root test suggested the adoption of a dynamic autoregressive distributed lag bounds testing procedure. The results confirmed the existence of a long-run equilibrium relationship between the outlined series within the period under investigation with a high speed of convergence. The ARDL equilibrium relationship shows that coal consumption is the largest emitter of carbon dioxide emissions in both short- (0.77%) and long- (0.86%) run. Economic growth was found to escalate CO2 emission by approximately 0.27% (in the short-run) and 0.19% (in the long-run). The Granger causality test indicates a non-causal effect between FDI inflow and economic expansion in South Africa, which implies that FDI is not a driver of economic advancement. The empirical study shows a bidirectional causal effect between urbanization and foreign direct investment. This suggests that urban development stimulates foreign direct investment in South Africa. The findings reveal a one-way link from GDP to coal consumption, suggesting economic prosperity promotes coal consumption. The study underscores that economic development and the attraction of more economic investments is in part, dependent on the conservative policy, development of urban centres through infrastructural improvement, and establishing industrial zones.
Keywords: 330; South Africa; coal consumption; CO2 emissions; climate change; urbanization